REMOVED: Oleosome interfacial engineering to enhance their functionality in foods - Saeed M. Ghazani; Erica Pensini; Jason Hargreaves; Analucia Mata; Burcu Guldiken; Alejandro G. Marangoni (Current Research in Food Science, 2023)
This article has been removed: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/policies/article-withdrawal).This article has been removed at the request of the authors due to unauthorized use of confidential data. Apologies are offered to the readers.